Frankenstein, Spinoza, and exemplarity. Issue 5 (28th May 2019) - Gatens, Moira
ABSTRACT: This paper reads Mary Shelley's novel, Frankenstein, through the lens of three themes in Spinoza's philosophy. First, the bondage of the passions; second, the importance of the imitation of affects as grounding sociability; and, finally, the problematic relationship between human normative life and the rest of nature, posed by Spinoza's immanent ontology. Like Spinoza's exemplars in the Ethics and in the Tractatus Theologico-Politicus, Shelley's presentation of the modern Prometheus is intended to provide her readers with a vivid salutary lesson: hubris and narcissism engender disastrous forms of sociability. In contrast, the ars vivendi of the wise person centres on strength of character ( fortitudo) which consists in achieving a balance between the care of one's self ( animositas ) and the care of others ( generositas ).